Barriers to application of weather and climate information in smallholder vegetable farming in Benguet - Sonny N. Domingo; Adrian D. Agbon; Ma. Divina Olaguera; Anna Jennifer L. Umlas; Katrina Mae C. Zuluaga; Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 2020)
Benguet province's comparative advantage in the cultivation of high value crops such as cabbage, carrots and potatoes are evident in the high volume of production experienced year on year. A reason for this is the province's favorable weather and climate; however, climate change may threaten the stability of the mountain farming systems in the coming years without proper measures for adaptation. This paper aims to understand the current barriers to the access and use of weather and climate information in agricultural decision making, as a means to cope with the changing climate. It was found that while farmers see the value of using weather and climate information, there is a lack of localized weather and climate information applicable to the microclimate of Benguet. The provision of information must also be supported with other interventions, such as access to low cost credit, to provide the other lacking resources farmers need to enact the optimal decision alternative.
Keywords: 330; weather and climate information; high value crops; smallholder farming; agriculture; decision analysis